Using Cartoon Films To Improve The Students’ Writing Ability at Eleventh Grade - Sri Hartini (Papanda Journal of English Education, 2022)
English teaching involves of four language skills, they are Listening, Speaking, Reading and Writing. Writing as a part of the difficult language skills besides listening, speaking and reading, must be taught maximally by the teacher to the students. The reason is because writing is a mixture of our idea, vocabulary and also grammar. Many students in SMAN 1 Bantarujeg still have poor ability in four skills, especially in writing. Those reasons because when they write something, they must pay attention in many things, including ideas, concepts, vocabulary and grammar. Besides that reason, there is a factor of students’ difficulties in writing text. It is the media of teaching. The objective of the research is to find out whether there is a significant difference between the students’ writing skill of narrative text of the eleventh grade students of SMA N 1 Bantarujeg in the academic year 2014-2015 who are taught by using cartoon film and those who are taught by using conventional teaching writing. The data were gathered from 11-14 April 2014. It was conducted as experimental study, and the data collection was test technique. The population in eight grade of SMAN 1 Bantarujeg are four classes with 114 students. Sample is a part of population that represents the whole population. If the population is 100 or less, it is better to take the whole population as the sample, if the population is more than 100 respondents, the writer can take 10-15 % or 20-25 % or more than 25% of the population based on the capability of a writers. The writer take 25% from the population as the sample. The calculating of determining sample are 25% x 114 = 29. So, the amount research sample are 29 students. XI IPA 1 with 28 students’, XI IPA 2 with 28 students’, XI IPS 1 with 29 students’, and XI IPS 2 with 29 students’. The writer used two classes: XI IPS 2 as the control group and XI IPS 1 as an experimental group. As the samples, the writer gave both classes different treatment, the experimental group was treated by using cartoon film technique while the control group was using conventional teaching writing technique. The data were processed by using t-test. The result shows that there is a significant difference between the group. The means of the data from the first and second data. The control group have means of pre-test is 72,9 and post test 75,17 while the experimental group have means of pre-test is 73,96 and post test is 77,758. Based on the t-test got the result is tobs = 3,59 , to = 2,78, t0.05 = 0,975 and df = 56. So, is the conclude that if to > t table it means that Ho is rejected and Ha is accepted, but when to < t table it means that Ho is accepted and Ha is rejected. Ha is accepted because to > tt ; 3,59 > 2.78 > 0,975. It’s means the result is significant and the hypothesis is accepted. However, the writer suggests the teacher should be more creative and innovative in selecting the suitable media in teaching learning. In addition, cartoon film can be used as alternative media to teach writing. So it will give some useful information about teaching writing by using cartoon films.